2020
DOI: 10.1186/s12711-020-00577-z
|View full text |Cite
|
Sign up to set email alerts
|

Direct and correlated responses to selection for autumn lambing in sheep

Abstract: Background Seasonal reproduction limits productivity, flexibility, and profitability in commercial sheep production. Hormonal and (or) photoperiodic manipulation can be used to control estrous cycles in sheep and reduce limitations that are imposed by the seasonal anestrous but are often impractical or incompatible with the extensive management systems preferred for ruminant livestock. Thus, the current study investigated the use of selection to improve realized fertility (i.e., the proportion of ewes that lam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…This result differs from studies in Romanov sheep reported by Murphy et al, where phenotypic variance (σ 2 P ) in litter size was low due to additive inheritance (0.06 to 0.08) and the influence of the permanent environment (0.05 to 0.07) in ewes [ 36 ]. Masood reported that in a linear model, the EBV of line S (beginning and end of the joining period for selection) fertility increased from −0.022 ± 0.040 in 1989 to 0.153 ± 0.044 in 2005; following a period of an out-of-season spring joining, the regression coefficient for EBV was 0.0101 ± 0.0004/year and the estimated heritability of the litter size was 0.04 ± 0.02, and the repeatability was 0.12 ± 0.03 [ 26 ]. For the heritability (0.08 to 0.09) and repeatability (0.10 to 0.12) for the number of lambs born on a per ewe lambing (NLBL) in Czech Romanov [ 37 , 38 ] and in Australian Merino sheep, the heritability of the litter size was 0.074 [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result differs from studies in Romanov sheep reported by Murphy et al, where phenotypic variance (σ 2 P ) in litter size was low due to additive inheritance (0.06 to 0.08) and the influence of the permanent environment (0.05 to 0.07) in ewes [ 36 ]. Masood reported that in a linear model, the EBV of line S (beginning and end of the joining period for selection) fertility increased from −0.022 ± 0.040 in 1989 to 0.153 ± 0.044 in 2005; following a period of an out-of-season spring joining, the regression coefficient for EBV was 0.0101 ± 0.0004/year and the estimated heritability of the litter size was 0.04 ± 0.02, and the repeatability was 0.12 ± 0.03 [ 26 ]. For the heritability (0.08 to 0.09) and repeatability (0.10 to 0.12) for the number of lambs born on a per ewe lambing (NLBL) in Czech Romanov [ 37 , 38 ] and in Australian Merino sheep, the heritability of the litter size was 0.074 [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that there were different degrees of correlation between the growth traits of Xinggao sheep. Others have reported in sheep heritabilities of the birth weight and body weight of lambs at 60, 90, and 120 days of age ranged from 0.015 to 0.19 [ 26 ]. Hanford et al [ 42 ] reported direct heritabilities of 0.25 for birth weight and 0.22 for weaning weight as well as maternal heritability of 0.20 for birth weight and 0.11 for weaning weight, and between the birth and weaning weights of direct genetic correlation it was 0.52.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation